Gamification resources in education: A theoretical approach - N. A. Astashova; S. K. Bondyreva; O. S. Popova (Russian State Vocational Pedagogical University, 2023)
Introduction. The modern education system has undergone serious changes in recent years - the content of educational programmes is being revised; electronic, mixed, mobile learning is being actively introduced; the practical activities of future specialists are being strengthened. The use of computer networks, web applications, and interactive services makes education more accessible, stimulating the cognitive interests of students, increasing motivation for education. One of the most significant innovative trends in modern education is gamification, which is most often considered as a system that uses components of computer games in non-gaming situations. Aim. The current research aims to analyse the conceptual foundations of gamification in education, to determine a system of tools that can present unique opportunities for gamification, features of its promising use for turning into an innovative experience in the development of higher professional education. Methodology and research methods. The study of the problem of gamification involves the analysis of pedagogical and psychological literature of foreign and Russian authors; systematisation and generalisation of pedagogical concepts, practice-oriented materials, and facts. The gamification methodology includes systematic, personality-oriented, activity-based approaches. An attempt is made to determine the components of the gamification system and their role in the organisation of modern education. The analysis of gamification resources makes it possible to identify approaches to increase motivation and involvement of students, and, in addition, to find out ways to include elements of game design (task definition, feedback, levels, creativity), computer games in the educational environment. On the basis of a personality-oriented approach, the influence of gaming technologies on the development of student personality is considered. The activity approach makes it possible to identify the basics of the organisation and management of the activities of subjects of education, to establish the features of the use of educational technologies, practices and methodological techniques. The activity-based approach in the context of gamification determines an active, ever-increasing activity as a source of personal development of students. Results. In the course of the research, the theoretical foundations of the use of gamification in modern higher education were formulated; tools for the prospective inclusion of gaming practices in the training system were identified; mechanisms of internal and external motivation of students, regulation of the behaviour of future specialists when using game elements were identified. Scientific novelty. The concept of gamification of education is part of the concept of the game and reflects the current trends in the development of education based on the strategy and tactics of gaming activities, structured in a special way taking into account the resources of game principles, mechanics, methods and techniques. Gamified learning can become a leader in the process of training specialists using innovative practices, stimulating motivation, regulating behaviour, implementing ideas of friendly competition and creative cooperation in various educational contexts. Practical significance. In the context of determining the promising foundations for the development of modern higher education, the ideas of original technological support for personnel training are proposed. The implementation of practical measures to develop the involvement of students in the educational process, the regulation of motivation, behaviour and practical activities of students, emotional self-realisation, and the system of relationships will contribute to improving the quality of education in higher education. An important result of the study was the conclusion about the expedient combination of traditional and innovative options for conducting training sessions with students, the inclusion of a variety of gaming practices in the educational process.